Inflammation and tuberculosis: host‐directed therapies. (19th May 2014) - Zumla, A.; Rao, M.; Parida, S. K.; Keshavjee, S.; Cassell, G.; Wallis, R.; Axelsson‐Robertsson, R.; Doherty, M.; Andersson, J.; Maeurer, M.
Abstract: Tuberculosis (TB) is an airborne infectious disease that kills almost two million individuals every year. Multidrug‐resistant (MDR) TB is caused by strains of Mycobacterium tuberculosis ( M. tb ) resistant to isoniazid and rifampin, the backbone of first‐line antitubercular treatment. MDR TB affects an estimated 500 000 new patients annually. Genetic analysis of drug‐resistant MDR‐TB showed that airborne transmission of undetected and untreated strains played a major role in disease outbreaks. The need for new TB vaccines and faster diagnostics, as well as the development of new drugs, has recently been highlighted. The major problem in terms of current TB research and clinical demands is the increasing number of cases of extensively drug‐resistant and 'treatment‐refractory' TB. An emerging scenario of adjunct host‐directed therapies is intended to target pulmonary TB where inflammatory processes can be deleterious and lead to immune exhaustion. 'Target‐organ‐saving' strategies may be warranted to prevent damage to infected tissues and achieve focused, clinically relevant and long‐lasting anti‐ M. tb cellular immune responses. Candidates for such interventions may be biological agents or already approved drugs that can be 're‐purposed' to interfere with biologically relevant cellular checkpoints. Here, we review current concepts of inflammation in TB disease and discuss candidate pathways for host‐directed therapies to achieve better clinical outcomes.